Designing a critical care solution using in-person and telemedicine approaches in the US-Mexico border area during COVID-19 - Venktesh R. Ramnath; Linda Hill; Jim Schultz; Jess Mandel; Andres Smith; Stacy Holberg; Lucy E. Horton; Atul Malhotra; Lawrence S. Friedman (Elsevier, 2021)
Background: UC San Diego Health System (UCSDHS) is the largest academic medical center and integrated care network in US-Mexico border area of California contiguous to the Northern Baja region of Mexico. The COVID-19 pandemic compelled several UCSDHS and local communities to create awareness around best methods to promote regional health in this economically, socially, and politically important border area. Purpose: To improve understanding of optimal strategies to execute critical care collaborative programs between academic and community health centers facing public health emergencies during the COVID-19 pandemic, based on the experience of UCSDHS and several community hospitals (one US, two Mexican) in the US-Mexico border region. Methods: After taking several preparatory steps, we developed a two-phase program that included 1) in-person activities to perform needs assessments, hands-on training and education, and morale building and 2) creation of a telemedicine-based (Tele-ICU) service for direct patient management and/or educational coaching experiences.Findings.A clinical and educational program between academic and community border hospitals was feasible, effective, and well received. Conclusion: We offer several policy-oriented recommendations steps for academic and community healthcare programs to build educational, collaborative partnerships to address COVID-19 and other cross-cultural, international public health emergencies.